Influence of conservation agriculture-based production systems on bacterial diversity and soil quality in rice-wheat-greengram cropping system in eastern Indo-Gangetic Plains of India - Kumar, Rakesh; Choudhary, Jaipal Singh; Naik, Sushanta Kumar; Mondal, Surajit; Mishra, Janki Sharan; Poonia, Shish Pal; Kumar, Saurabh; Hans, Hansraj; Kumar, Sanjeev; Das, Anup; Kumar, Virender; Bhatt, Bhagwati Prasad; et al. (Frontiers in Microbiology, 2023)
Conservation agriculture (CA) is gaining attention in South Asia as an environmentally benign and sustainable food production system. The knowledge of the soil bacterial community composition along with other soil properties is essential for evaluating the CA-based management practices for achieving the soil environment sustainability and climate resilience in the rice-wheat-greengram system. The long-term effects of CA-based tillage-cum-crop-establishment (TCE) methods on earthworm population, soil parameters as well as microbial diversity have not been well studied. Seven treatments (or scenarios) were laid down with the various tillage (wet, dry, or zero-tillage), establishment method (direct-or drill-seeding or transplantation) and residue management practices (mixed with the soil or kept on the soil surface). The soil samples were collected after seven years of experimentation and analyzed for the soil quality and bacterial diversity to examine the effect of tillage-cum-crop-establishment methods. Earthworm population (3.6 times), soil organic carbon (11.94%), macro (NPK) (14.50-23.57%) and micronutrients (Mn, and Cu) (13.25 and 29.57%) contents were appreciably higher under CA-based TCE methods than tillage-intensive farming practices. Significantly higher number of OTUs (1192±50) and Chao1 (1415.65 ± 14.34) values were observed in partial CA-based production system (p<0.05). Forty-two (42) bacterial phyla were identified across the scenarios, and Proteobacteria, Actinobacteria, and Firmicutes were the most dominant in all the scenarios. The CA-based scenarios harbor a high abundance of Proteobacteria (2-13%), whereas the conventional tillage-based scenarios were dominated by the bacterial phyla Acidobacteria and Chloroflexi and found statistically differed among the scenarios (p<0.05). Composition of the major phyla i.e., Proteobacteria, Actinobacteria, and Firmicutes were associated differently with either CA or farmers-based tillage management practices. Overall, the present study indicates the importance of CA-based tillage-cum-crop-establishment methods in shaping bacterial diversity, earthworms population, soil organic carbon, and plant nutrient availability, which are crucial for sustainable agricultural production and resilience in agro-ecosystem.